Replenishment of vitamin A for 7 days partially restored hepatic gene expressions altered by its deficiency in rats - Zhang, Yan; Tian, Kui; Chen, Guoxun (Frontiers in Nutrition, 2022)
We investigated the effects of vitamin A (VA) status on metabolism of Zucker rats with different genders and genotypes, and of short-term refeeding of a VA sufficient (VAS) diet on VA deficient (VAD) animals. First, male and female Zucker lean (ZL) and fatty (ZF) rats at weaning were fed a VAD or VAS diet for 8 weeks. Second, VAD ZL rats were fed a VAS diet for 3 (VAD-VAS3d) or 7 (VAD-VAS7d) days. The body weight (BW), blood parameters and hepatic expressions of genes for metabolism were determined. VA deficiency reduced BW gain in ZL and ZF rats of either gender. VAD ZL rats had lower plasma glucose, insulin, and leptin levels than VAS ZL rats. VAD-VAS3d and VAD-VAS7d rats had higher plasma glucose, insulin and leptin levels than that in the VAD rats. The hepatic mRNA levels of Gck, Cyp26a1, Srebp-1c, Igf11, Rarb, Rxra, Rxrg, Pparg, and Ppard were lowered by VA deficiency. Refeeding of the VAS diet for 3 days restored the Gck and Cyp26a1 expressions, and for 7 days restored the Gck, Cyp26a1, Igf1, Rarb and Rxrb expressions significantly. The 7-day VA replenishment partially restored the hepatic gene expressions and metabolic changes in VAD ZL rats.